2021
DOI: 10.5498/wjp.v11.i11.1106
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and resilience mediate the relationship between childhood exposure to domestic violence and posttraumatic growth/stress disorder during COVID-19 pandemic

Abstract: BACKGROUND Studies have indicated that childhood exposure to domestic violence is a common factor in posttraumatic growth (PTG) and posttraumatic stress disorder (PTSD), but it is unclear whether PTG and PTSD share a common/different underlying mechanism. AIM To explore the common/different underlying mechanism of PTG and PTSD. METHODS Between February 12 and 17, 2020, a nationwide cross-sectional online survey was conducted in China among 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It can be concluded that self-compassion is sufficient to influence the increase in post-traumatic growth in women who are victims of husbands' infidelity. Individuals with high levels of self-compassion will be able to gather resources for themselves when experiencing traumatic events thus they can better cope with stress (Chi et al, 2021). In this study, resilience is a moderating predictor variable that is not statistically significant but still plays a role in the relationship model (Ghozali, 2017).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be concluded that self-compassion is sufficient to influence the increase in post-traumatic growth in women who are victims of husbands' infidelity. Individuals with high levels of self-compassion will be able to gather resources for themselves when experiencing traumatic events thus they can better cope with stress (Chi et al, 2021). In this study, resilience is a moderating predictor variable that is not statistically significant but still plays a role in the relationship model (Ghozali, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…Self-Compassion is one of the variables that play a role in the level of posttraumatic growth that is owned by a person. Based on research (Chi et al, 2021) shows as selfcompassion has a relationship with posttraumatic growth. The purpose of this study was to examine the effect of self-compassion on posttraumatic growth in wives as victims of husbands' infidelity with resilience as a moderating variable.…”
Section: Introductionmentioning
confidence: 99%
“…With the accelerated spread of the Omicron variant, a specific “city-wide lockdown” was imposed in Shenzhen lasting for 10 days. This home confinement negatively influenced resident's physical and mental health ( Chi et al, 2020 ; Chi et al, 2021 ; Hosen et al, 2021 ; Hossain et al, 2020 ; Solmi, 2022 ) as it was a driver of a series of unhealthy behaviors including the decrease of regular pyhsical activity (PA) and the increase of sedentary behaviour ( Chen et al, 2020a , 2020b ; Guerrero et al, 2020 ; Lin et al, 2020 ; Racine et al, 2021 ; Stockwell et al, 2021 ). The latter was exacerbated by the fact that Shenzhen as a highly developed area in China with high prices of commodities and housing conditions resulting in crowded living.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience refers to the capacity of a system to adapt successfully to significant challenges that threaten its function, viability, or development [ 21 ]. Prior studies consistently found that resilience, as a crucial character strength, is an important asset that helps young people cope with COVID-19, bounce back, and even grow from the pandemic to gain personal development [ 22 24 ]. These studies suggest that young people with higher levels of resilience would be more prone to experience positive changes.…”
mentioning
confidence: 99%